A Wireless Location System for Sensing the Relative Position between Mining Vehicles - Khrebtov, Pavel; Pöttker, Alois; Max, Stephan; Vossiek, Martin (2007 IEEE Instrumentation and Measurement Technology Conference, 2007)
In this paper a novel system and concept for sensing the relative position between mining vehicles is introduced. The localization is based on secondary radar like distance measurements between radar basestations on the excavator and transponders on the truck. Based on a novel geometry-matching algorithm it is possible to determine the relative position between truck and excavator precisely even in complex measurement and environmental conditions. The geometry-matching algorithm overcomes problems of usual triangulation based approaches because it efficiently reduces the risk to get an underdetermined set of geometric equations in conditions where measuring paths are shadowed or disturbed. The proposed concept allows for a steady and flexible control of all movements of the truck relative to an excavator and thus can contribute effectively to increase automation and productivity in future mining systems. The results of first full-scale experiments show the consistency and good performance of the proposed approach. © 2007 IEEE.
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.LEH.awirel
Keywords: Automation; Local positioning; Mining vehicle location monitoring; Secondary radar